A method for assessing infrastructure for CO2 utilization: A case study of Finland. (1st November 2017) - Karjunen, Hannu; Tynjälä, Tero; Hyppänen, Timo
Highlights: Modeling tool is presented for comparing carbon capture and utilization strategies. The temporal disparity between CO 2 production and consumption is identified. Key decisions defining a general carbon utilization system are proposed. Abstract: Synthetic hydrocarbons can be produced sustainably with power-to-gas processes, resulting in a net reduction of greenhouse gas emissions due to the substitution of conventional natural gas and other fossil fuels with carbon-neutral alternatives. Acquisition of the CO 2 for the synthetic fuel production can be implemented in multiple ways. This work introduces a node-based model to assess different implementation strategies of CO 2 utilization systems, taking into account temporal effects, regional variation, and economies of scale for CO 2 capture. Intermediate storage volumes, capture costs, transport quantities, and other relevant infrastructural aspects of the CCU system can be estimated with the model. Finland is used as a case study, focusing specifically on the national and regional scale. CO 2 capture costs are significant, being nearly four times larger than the cost of storage in the baseline scenario (354 M€, 85 M€). CO 2 sources with smaller annual emissions increases capture costs by 14% compared to baseline. This increase in cost is comparable to the cost of transporting over a quarter of all captured CO 2 to off-site processing (varying distance, 100–400 km). Seasonal storage of CO 2 is found to be beneficial for the cost-efficient production of synthetic fuels, owing to the temporal disparity between CO 2 emissions and utilization, as well as the overall cost structure of the components. Five key decision categories are proposed for a carbon utilization system: scale, type, units, location, and technological decisions. These may be applied to describe any carbon utilization system, helping to form a more comprehensive picture of a future energy system, where carbon is widely used as a raw material.